2019
DOI: 10.3390/catal9020108
|View full text |Cite
|
Sign up to set email alerts
|

Ru-Ti Oxide Based Catalysts for HCl Oxidation: The Favorable Oxygen Species and Influence of Ce Additive

Abstract: Several Ru-Ti oxide-based catalysts were investigated for the catalytic oxidation of HCl to Cl2 in this work. The active component RuO2 was loaded on different titanium-containing supports by a facile wetness impregnation method. The Ru-Ti oxide based catalysts were characterized by XRD, N2 sorption, SEM, TEM, H2-TPR, XPS, and Raman, which is correlated with the catalytic tests. Rutile TiO2 was confirmed as the optimal support even though it has a low specific surface area. In addition to the interfacial epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In reduction temperatures ranging from 50 to 250 °C, the peaks below 200 °C are ascribed to the reduction of surface RuO 2 species while the peaks above 200 °C are assigned to the reduction of bulk RuO 2 species, including Ru–O–Ru and Ru–O–Ti species. 28,43 It is noteworthy that the H 2 consumption peak related to surface RuO 2 reduction tends to shift to a higher reduction temperature with increasing calcination temperature for RuO 2 /TiO 2 -150, RuO 2 /TiO 2 -200, and RuO 2 /TiO 2 -250, due to the oxidation of Ru 3+ to Ru 4+ . It is reported that the reduction temperature of Ru–O–Ti is higher than that of Ru–O–Ru.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In reduction temperatures ranging from 50 to 250 °C, the peaks below 200 °C are ascribed to the reduction of surface RuO 2 species while the peaks above 200 °C are assigned to the reduction of bulk RuO 2 species, including Ru–O–Ru and Ru–O–Ti species. 28,43 It is noteworthy that the H 2 consumption peak related to surface RuO 2 reduction tends to shift to a higher reduction temperature with increasing calcination temperature for RuO 2 /TiO 2 -150, RuO 2 /TiO 2 -200, and RuO 2 /TiO 2 -250, due to the oxidation of Ru 3+ to Ru 4+ . It is reported that the reduction temperature of Ru–O–Ti is higher than that of Ru–O–Ru.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation has been reported in supported RuO 2 catalysts by others. 11,43 In combination with the results from the XPS, Raman, and H 2 -TPR characterization studies, the effects of calcination temperature on the structure and electronic properties of the RuO 2 species in the catalysts are clear. The surface RuO 2 amount increases with increasing calcination temperature for preparing the catalysts, from 150 °C to 250 °C, due to the oxidation of Ru 3+ to Ru 4+ .…”
Section: Catalyst Characterizationmentioning
confidence: 91%
“…The Raman shifts suggest that the rutile structure of RuO 2 is modified, according to the changed RuO 2 interfacial interactions, substantially as a result of electron transfer from RuO 2 to Al−MgF 2 . 54 The morphological characteristics of RuO 2 /Al−MgF 2 -400 were scrutinized by TEM. As displayed in Figure 4, some dark edges and layers are presumed to be the dispersed RuO 2 phase, which is consistent with the observations from the literature.…”
Section: Acs Catalysismentioning
confidence: 99%
“…From the deconvolution of the O 1s spectrum (Figure 5d), two peaks were defined, namely O1 and O2, centered at biding energies of 529.6 eV and 531.5 eV, respectively. These peaks can be attributed to metal-oxygen bonds of the RuO 2 and NiO dopants, as well as to defects in the SrTiO 3 semiconductor [40][41][42]. The absence of peaks above 531.5 eV may indicate that there is no chemical adsorption of oxygen in the sample [40].…”
Section: Characterization Of the Photocatalystsmentioning
confidence: 99%